Parents’ Attitudes Towards Drug Addiction of Young Patients of Disaccustoming Clinics (Archives of Criminology, 1991)
The paper presents the finding of a longitudinal study of two problems: the addicts’ prospects of quitting drugs, and  the psycho-social factors conducive to success in this respect.The first study (conducted in the years 1974–1976) concerned all patients aged 15–28 treated in that period for repeated taking of drugs, at the disaccustoming clinic for young persons and at district clinics for adults in the city of Łódź. The total of 107 patients were examined (23 per cent of girls and 77 per cent of young men). According to medical diagnosis, 21 per cent of them suffered from a social, 50 per cent – from a psychological, and 29 per cent – from a physical dependence. After about 10 years, a catamnesis was carried out which concerned 80 patients. The methods applied in both parts of the study were: detailed interviews with the patients and their families; medical examination; and  analysis of a variety of documents.For the estimation of the fates of the sample, the following issues were of the key importance: persistence in or abandonment of addiction; permanence of abstinence; and the extent of self-dependence achieved. This complexity of the examined persons’ situation taken into account, the following criteria of improvement have been adopted: a) medical (persistence in abstinence); b) psychological (psychological acceptance of abstinence and the resulting change of lifestyle); and c) social (active engagement in the appropriate social roles). Basing on the above criteria, the following categories were distinguished within the sample:1) persons who persisted in addiction; 2) deceased in consequence of addiction; 3) those who quit taking drugs but still had various problems resulting from their former addiction; and 4) those who quit and had no special problems.Against previous expectations, persons who kept taking drugs (26 per cent) did not constitute the mos tnumerous group. Their mean period of taking drugs was 13.6 years. Their interests and social contacts were narrowed to problems related to the taking and production or obtaining drugs. They were generally emaciated and had increasing withdrawal symptoms. Persons of this group went through several months’periods of abstinence due to treatment, imprisonment, or a favourable occurrence in their lives. All of them, however, relapsed into addiction quite promptly, particularly when faced with unavoidable difficulties. Family life or married persons in this group was unhappy, and most marriages broke up: only those between two addicts still lasted.Biographies similar to those discussed above were also found in the case of persons (9 per cent) who died during catamnesis in circumstances that pointed to their death’s relationship with the taking of drugs and with addiction, interpreted also as a certain lifestyle. All persons of this group had been taking drugs for a long time (over five years), and their death was due either to serious diseases combined with emaciation, or occurred in unexplained circumstances as a border-line case between accident, suicide, and homicide.3.The largest group (46 per cent) consisted of persons who admittedly quit taking drugs but still had various health and social problems related to their previous addiction. Their main problems were as follows: in the sphere of physical health, chronic gastritis, entero-gastric disorders. diseases of liver, heart probiems, reduced physical endurance, disturbances of sleep, and in the sphere of mental health: anxiety, hypersensibility, difficulties in establishing relations with others, depression, low selfesteem, lack of self-confidence, high emotional instability, latent inward anxiety, etc. The most important and frequent social problems included leaving secondary school and the related subsequent lack of professional qualifications, a more difficult start into adult life, the need to relinquish certain professional aspirations and a more interesting job, and a lack of prospects of promotion. In most respondents, this caused a sense of instability and inevitably gave rise to frustrations, increasing their passiveness and apathy. This situation was particularly painful for persons whose intellligence had been rather high before they started taking drugs and who used to have various interests and aspirations. The coincidence of the ahove circumstances also negatively affected their family and marital situation. The fates of persons who quit after several years of taking drugs seem to indicate that those persons’ tolerance to stress and ability to overcome difficulties had been greatly impaired during the period of addiction: as a consequence, they were subsequently unable to cope even with everyday matters which they perceived as great problems.The last group consisted of persons (19 per cent) who had been taking drugs for a shorter period as a rule (not longer than five years in general), and who were not only able to persist in abstinence during catamnesis but also met the psychological and social criteria of improvement. A high proportion of girls in this group (over 50 per cent) seems characteristic. Moreover, nearly all those persons were married: their marriages, happy as a rule, were a great assistance to them.Therefore, the total of 65 per cent of the sample succeeded to quit addiction. What was crucial here was not exactly the form of dependence (social, psychological, physical) but rather the length of the period of taking drugs. If a person has been taking drugs for over five years, his prospects of improvement diminish greatly, and favourable results can only be obtained in the course of a prolonged rehabilitation.The reasons that made most persons in the sample abandon their addiction were seeked both in their personality traits and family environments. What is characteristic is that a considerable portion of respondents come from the intelligentsia, with an average or even high social status and good material situation (in which respect they differ greatly from e.g. juvenile delinquents or young alcoholics). There is in such families a rather small extent of pathology such as alcoholism, crime, or prostitution. In most cases, the parents’ attitude to their children’s taking of drugs should be estimated as proper. The parents played an effective role, fighting for their children to quit as a general rule. Aware of the dangers related to drugs, they took energetic steps which consisted among others in changing the child’s environment (e. g. moving with him to another town), inducing him to undergo treatment and organizing that treatment, supervising his leisure activities, etc. Parents’ improper attitudes such as scenes, turning the child out, etc., were most seldom.The analysis of the reasons which made about two-thirds of respondents quit addiction included their character and intellectual traits defined in the course of psychiatric examination. There was in the sample a rather large number of individuals with the so-called immature personality, who at the age of about 25 were still characterized by traits such as a passive attitude to life; inconsideration for their own future; a poorly developed critical attitude towards themselves and their situation; emotional immaturity; dependence on others (e.g. the mother or friends); inabitity to act effectively, to overcome obstacles and to achieve distant aims; easy discouragement when faced with difficulties, etc. It was only during catamnesis, at the age of about 25, that the respondents’ former, largely childish attitudes were transformed with delay into normal traits of young persons. This development and the crystallization of personality, connected with the parents’ activities and their proper attitude towards the children’s addiction, were conducive to abandonment of addiction by, a considerable portion of the sample. Other factors which played this favourable role in the respondents’ biographies were: a rather high intellectual level; the “psychological shock” caused e.g. by detoxification at a mental hospital or the death of a close friend due to overdose; and imprisonment and going through the withdrawal syndrome in such conditions, etc.To interpret the findings, the conception of American alcohologist J. Ewing has been used: it speaks of inducing and protecting factors in the development of alcoholism. According to Ewing, an individual who starts taking drugs regularly is influenced by a number of biological, psychological, and social factors, some of them conducive to the development of addiction and others protecting the individual against it. Despite the opinions of some researchers, “protecting” factors prove strong enough to hold back even an already addicted person and to contribute to his abandonment of drugs. With the prolongation of the period of taking drugs, the influence of protecting factors wanes, and that of the ones which induce the individual to continue the taking of drugs and thus foster a further development of addiction spreads. The following practical conclusions have been drawn from the study:– Intensified therapeutic and rehabilitative treatment, during the first years of taking drugs in particular.– Co-operation with the addicts’ parents who should be instructed (e.g. about the ways of soothing difficulties in adjustment); whose activity should be assisted, e.g. through the organization of parents’ self-help associations; whose contacts with specialist clinics should be made easier, etc.– Creation of possibilities of medical and rehabilitative treatment for various cotegories of young persons addicted to drugs (not all of them feel comfortable in the existing centres, e.g. of the MONAR movement).– Short-term hospital treatments are reasonable at the initial stage of addiction (several years of taking drugs), as in that period the addicted person’s power of resistance can be strengthened inherent both in his personality and the environment.Help and care should be provided for addicts who have already drugs but have life problems caused or aggravaquited by their previous addiction.